Programa de afrontamiento para sindrome de burnout en médicos especialistas en cirugía general de los Hospitales de 2do nivel de la ciudad de Riobamba - Huilca Logroño, Luis Fernando (2018)
Maslach and Jackson in 1981 defined Burnout Syndrome as a psychosocial risk at work as an inadequate response to chronic stress characterized by three dimensions: emotional exhaustion, depersonalization and lack of personal fulfillment at work. This syndrome is a set of signs and symptoms whose purpose is to feel burned with work and go through the phases described formally. The main objective was to demonstrate that the coping program reduces the Burnout Syndrome of the General Surgery physicians of the 2nd Level Hospitals of the City of Riobamba, the research design belongs to the application, transversal, correlational and field type . The Deductive method is used. The technique for data collection is the test and the instrument the brief "Burnout" questionnaire (CBB). A Passive Music Therapy program was applied in surgical procedures in addition to work gymnastics for discomfort of the neck, arms, and waist. The population is 16 Specialists in General Surgery of the second level hospitals of the city of Riobamba. Results: The Burnout Syndrome is transformed from 100% medium to 25% low and 75% medium. Hypothesis: Through a Chi square test, 3 hypotheses are checked: 1.- The coping program decreases the Burnout Syndrome of General Surgery physicians obtaining physiological, physical and mental relaxation, 2.- The coping program with the application of passive music therapy decreases the levels of Burnout Syndrome of General Surgery specialists improving the components emotional exhaustion and depersonalization, 3.- The coping program by performing work gymnastics reduces the levels of Burnout Syndrome of General Surgery specialists improving Symptoms in the neck, arms and hips.